2010
DOI: 10.1364/oe.18.005245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency, MTF and chromatic properties of four diffractive bifocal intraocular lens designs

Abstract: International audienceThe aim of this paper is to compare the properties of four different profiles which can be used as multifocal intraocular lens. The Hankel transform based on the theory of scalar diffraction is applied to a binary profile, a parabolic one, a parabolic profile with holes, and finally a sinusoidal one. This enables to study the various distributions of the diffractive efficiencies and the axial chromatism. The image quality is evaluated by means of simulations of the MTFs with Zemax®. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 7 publications
(14 reference statements)
0
36
0
1
Order By: Relevance
“…The expected light distribution between the three foci as provided by the manufacturer is shown in Figure 2. It is worth emphasizing that this distribution of energy is indeed the theoretical diffraction efficiency [15,23] of the far, intermediate and near foci of the IOL. Since the amount of the energy transmitted by the trifocal IOL and sent to each of the foci is proportional to this diffraction efficiency, it is generally assumed that the theoretical light distribution showed in Figure 2 will correspond to the energy correctly focused onto the respective image planes.…”
Section: Iol Characteristicsmentioning
confidence: 73%
See 2 more Smart Citations
“…The expected light distribution between the three foci as provided by the manufacturer is shown in Figure 2. It is worth emphasizing that this distribution of energy is indeed the theoretical diffraction efficiency [15,23] of the far, intermediate and near foci of the IOL. Since the amount of the energy transmitted by the trifocal IOL and sent to each of the foci is proportional to this diffraction efficiency, it is generally assumed that the theoretical light distribution showed in Figure 2 will correspond to the energy correctly focused onto the respective image planes.…”
Section: Iol Characteristicsmentioning
confidence: 73%
“…Finally, additional (although presumably small) contributions to the background may also come from higher diffraction orders. [23] The performance of the intermediate focus deserves further explanation. We have found that for IOL-pupils up to 3.0 mm approximately, the experimental energy efficiency of this focus is, somehow surprising, larger than the provided values of diffraction efficiency (Figure 8), the smaller the pupil the larger the difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally it is worth to mention that the experimental analysis of chromatic properties of MIOLs [18,19] is readily possible with our proposal simply by changing the light source. …”
Section: Discussionmentioning
confidence: 99%
“…There is a great interest to determine either in a test bench [43], [44] or in clinical studies [45], [46] the conditions and the degree to which the aspheric design in apodized diffractive multifocal IOLs might be advantageous versus a conventional spherical design, particularly when some studies have shown little or no benefit of aspheric IOLs with small pupils [47, [48]. For the assessment of the optical performance of multifocal IOLs, the common metrics (point spread function, modulation transfer function, and visual acuity) have to be measured [38], [49][50][51][52] and also its behaviour in terms of the energy balance between the distance an near images and its variation with the pupil diameter. Very recent studies carried out in an optical bench show a discrepancy between the theoretical prediction of the design and the experimentally measured energy distribution between the two foci in apodized diffractive multifocal IOLs [53].…”
Section: Model Eyes For Iol Testingmentioning
confidence: 99%